1998
DOI: 10.1038/sj.gt.3300680
|View full text |Cite
|
Sign up to set email alerts
|

Adeno-associated virus vectors can be efficiently produced without helper virus

Abstract: The purpose of this work was to develop an efficient Therefore the minimum set of genes required to produce method for the production of adeno-associated virus (AAV) AAV helper activity equivalent to that provided by adenvectors in the absence of helper virus. The adenovirus ovirus infection consists of, or is a subset of, the following regions that mediate AAV vector replication were identified genes: the E4orf6 gene, the 72-M r , E2A protein gene, the and assembled into a helper plasmid. These included the V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
321
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 464 publications
(328 citation statements)
references
References 35 publications
3
321
0
Order By: Relevance
“…AAV vectors (AAV-GDNFflag and AAV-LacZ) were purified using two sequential continuous CsCl gradients, as described previously. 40 The final particle titer of the Gene Therapy AAV-GDNFflag was 1.6 × 10 13 vector genome copies/ml and AAV-LacZ was 2.1 × 10 13 vector genome copies/ml, as estimated by quantitative DNA dot-blot hybridization analysis.…”
Section: Methodsmentioning
confidence: 96%
“…AAV vectors (AAV-GDNFflag and AAV-LacZ) were purified using two sequential continuous CsCl gradients, as described previously. 40 The final particle titer of the Gene Therapy AAV-GDNFflag was 1.6 × 10 13 vector genome copies/ml and AAV-LacZ was 2.1 × 10 13 vector genome copies/ml, as estimated by quantitative DNA dot-blot hybridization analysis.…”
Section: Methodsmentioning
confidence: 96%
“…4,22,24 The mechanism(s) underlying the effect of the adenovirus genes on recPV production and which elements, among the ones expressed by the pXX6 plasmid, are required for the amplification, remain uncharacterized. Similar studies conducted with adeno-associated viruses showed that E2a is the major contributor to the adenoviral helper effect on AAV-2, 23 whereas VA RNA sustains the AAV-5 replication by blocking double-stranded RNA-activated protein kinase activation and suppressing the antiviral cellular response. 20 This study shows that pXX6 significantly increases and accelerates viral DNA replication during the production of recPVs.…”
Section: Discussionmentioning
confidence: 56%
“…Transfection of HEK 293T cells with either pAd5DE1DE3 (containing all adenovirus-5 genes with the exception of E1 and E3), pXX6 or pVAE2AE4-5 (both containing the adenovirus-5 genes E2a, E4(orf6) and VA RNA) led to a comparable increase in recPV production. These results indicate that, similarly to AAV and B19, 22,23 the adenoviral genes contained in pXX6 are sufficient to increase recPV production. It is likely that the protocols used here can be further improved for instance by determining the most appropriate timing for the delivery of the adenovirus genes to producer cells or the optimal molar ratio of the three plasmids used for the production (parvovirus vector: Adenovirus genes enhance parvovirus production N El-Andaloussi et al capsid vector: adenoviral helper).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations